PENGARUH MODEL PEMBELAJARAN INVESTIGASI KELOMPOK SISWA SMP KELAS VIII TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKn - Fatolosa Hulu (Jurnal Education and Development, 2020)
This study aims to determine how the effect of the Group Investigation Learning Model Against Learning Outcomes of PPkn Class VIII Middle School 1 Gomo. This research uses a quantitative approach with an experimental nature. Research subjects were divided into two class groups namely control class and experimental class. The subjects of the study were the students of class VIII A and VIII B of SMP Negeri 1 Gomo, amounting to 38 students, consisting of 18 male students and 20 female students. Based on the results of the study, the following results were obtained: for the initial tests in the experimental class amounted to 60.13 (VIII-A) with sufficient categories while for the control class amounted to 57.89 (VIII-B). Students who are taught using the Group Investigation learning model with an average score of 81.96 (VIII-A) in both categories and in the Control Class with an average value of 67.28 (VIII-B) on the sub-topic of Employment. Based on the calculation of the hypothesis test obtained ttable = 1.729, so tcount> namely: 3.832. This shows the value of t> t table. Because tcount> ttable, Ha is accepted and Ho is rejected, in other words, there is an influence of the learning model of group investigation on the learning outcomes of PPkn in class VIII of SMP Negeri 1 Gomo. Based on these results, the study provides a number of suggestions, namely: (1) researchers' expectations of the PPKn subject teacher should use the learning model Investigating this group as an alternative material in the learning process to be more effective and correct any weaknesses and shortcomings of researchers in this study, (2 ) The next research should be a reference material for conducting research that is relevant to this research